2016
DOI: 10.1177/0218492316629851
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of pneumonectomy in a tertiary center

Abstract: Our mortality for pneumonectomy was 50% less than the national mortality rate and significantly lower than that predicted by the Thoracoscore for lung cancer. This confirms that pneumonectomy is still an effective modality for the treatment of lung cancer, with low operative mortality and good long-term survival, especially in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Some studies have similar results. Qadri et al 19 reported median survival was better in left pneumonectomy (left 2.7 years vs. right 1.9 years), as well as an improved long-term survival (Log-rank P =0.006). Fernandez and associates 18 reviewed 9746 patients underwent pneumonectomy in the Surveillance, Epidemiology, and End Results (SEER) database, and found a right pneumonectomy is correlated with almost twice the perioperative mortality as a left pneumonectomy.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have similar results. Qadri et al 19 reported median survival was better in left pneumonectomy (left 2.7 years vs. right 1.9 years), as well as an improved long-term survival (Log-rank P =0.006). Fernandez and associates 18 reviewed 9746 patients underwent pneumonectomy in the Surveillance, Epidemiology, and End Results (SEER) database, and found a right pneumonectomy is correlated with almost twice the perioperative mortality as a left pneumonectomy.…”
Section: Discussionmentioning
confidence: 97%
“…Pneumonectomy is a rare procedure in pulmonary surgery perioperative mortality to 3.3% (8). In our institute, 30-day mortality of 100 patients under pneumonectomy was 4.0%.…”
Section: Discussionmentioning
confidence: 76%
“…For patients undergoing pneumonectomy, some recent studies have indicated that it may overestimate mortality in high risk groups, whilst underestimating risk in low risk groups 55 . When applied to a large UK-based population it appeared to generally overestimate mortality 56,57 .…”
Section: Thoracoscorementioning
confidence: 94%